Redesign of corporate intranets and a revival of old debates: menus vs search engines - García-Morales, Elisa (Anuario ThinkEPI, 2015)
Many companies are addressing the redesign of their corporate intranet. There is an open discussion on the use of search engines compared to navigation menus; those subjects were already discussed in the 90s, with the first intranet generation. In our judgement, the great improvements in search engine capabilities do not replace the need for good classification and taxonomy structures in intranet architecture.
Keywords: Intranet; Taxonomy; Classification; Sharepoint 2013; Social intranet; Enterprise search.